Small Fractures Caused by the 2019 Ridgecrest Earthquake Sequence: Insights From 3D Coseismic Displacement and Uniaxial Loading Rock Experiments - Xu, Andong; Zhao, Yonghong; Wang, Teng; Ren, Chunmei; Yue, Han (Frontiers in Earth Science, 2021)
The moment magnitude (Mw) 6.4 and 7.1 Ridgecrest earthquake sequence occurred on 4th and 6th July 2019, ruptured a conjugate fault system within the eastern California shear zone. In addition to the ~50 km surface ruptures, the sequence activated a series of structures with lengths ranging from 1 to 10 km, which are well illuminated by phase gradient maps of Synthetic Aperture Radar (SAR) interferograms. The deformation patterns and mechanisms of these fractures has been well studied, yet the controlling factors of their spatial distribution are less discussed, which are important for understanding how the accumulated strain is released via distributed faulting in the earthquake cycle. Here, we use multi-source SAR images to derive 3-dimensional (3D) surface displacement along the main ruptures and the 2-dimensional (shear and normal) deformation across the detected small fractures caused by the 2019 Ridgecrest earthquake sequence. We find that the distribution of these fractures is related to the displacement pattern along the main rupture. Specifically, more fractures appeared in areas with tensile strain normal to the main rupture. We also conduct uniaxial loading rock experiments to evaluate the strain distribution before the samples were broken. Rock experiments show that rupturing of a conjugated fault system may produce local strain concentration along the main rupture, indicating the important role of the fore-shock rupture in generating small fractures with different striking angles and deformation patterns. The 2019 Ridgecrest earthquake sequence exhibits complicated crust behaviors by rupturing an immature fault system, implying that the simple elastic rebound theory may be insufficient to model the coseismic deformation during the earthquake cycle, particularly in the zone with weak crust.